The Effect of Online Learning and Teacher Pedagogic Competence on Independent Learning of Students in Class Xi Otk 1 and 3 (Study at Smk Negeri 1 Patumbak Medan) T.P 2021/2022 - Sindy Ayu Handari (Outline Publisher, 2022)
The problem in this research is that the students' learning independence has not been maximized in learning, the lack of motivation and responsibility in students and the low activeness of students in the teaching and learning process. The purpose of this study was to determine whether there was an effect of online learning and teacher pedagogic competence on the learning independence of students at SMK Negeri 1 Patumbak Medan. The population of this study were all students. The type of this research was SMK Negeri 1 Patumbak Medan Class XI OTKP 1 and 3. With a sample of 70 students. Data collection techniques using documentation and questionnaires. The data analysis technique uses Validity Test, Reliability Test, Normality Test, Linearity Test, Heteroscedasticity Test, T and F Test. The results of multiple linear regression are Y = 89.412 + 0.160X1 + 0.152X2. With the results obtained tcount 3.053 < ttable 1.995 with a significant 0.003 <0.05 explaining that there is an effect of online learning on learning independence. Then the value of tcount 4.484 < ttable 1.995 with a significant 0.000 <0.05 explains that the teacher's pedagogic competence has a positive and significant effect on student learning independence and Fcount 11.472 > Ftable 3.13 with a significance of 0.000 <0.05 explaining that online learning and competence The teacher's pedagogy has a positive and significant effect together on student learning independence.